REALISME DALAM KEPENTINGAN NASIONAL INDONESIA MELALUI FORUM KONFERENSI ASIA AFRIKA (KAA) DAN GERAKAN NON BLOK (GNB) - Taufan Herdansyah Akbar; Agus Subagyo; Jusmalia Oktaviani (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2020)
Realism is an approach and paradigm that is in international relations, Realism began to be debated during World War II (World War II) because of the failure of the League of Nations (LBB). LBB is the brainchild of idealists who are considered to have failed to prevent war and create peace. Realism existed even before the paradigm debate which was later called classical realism with one of its characters being Niccolo Machiavelly. Niccolo Maciavelly's style of realism emphasizes that human nature is egositically and creates an anarchic world. In this study the research team wanted to prove that what Niccolo Machiavelly delivered was not merely increasing military power merely to create peace, but negotiation and diplomacy methods were also instruments of the State in achieving its national interests in realism like Indonesia. The national interests of Indonesia are everything for Indonesian politicians and the existence and power of Indonesia is the goal of Indonesia's interests to avoid war. Therefore Indonesia must have played its role in the Asian-African Conference and the Non-Aligned Movement at that time as an instrument of achieving national interests in Realism. This research will use qualitative research methods with a historical approach. The results of this study provide answers that Realism is not merely militaristic but also a role as a rational actor.